1998
DOI: 10.1093/toxsci/42.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidative Stress in Brain Tissues of Mice after Subchronic Exposure to 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: The ability of single doses of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) to induce oxidative stress in hepatic and some extrahepatic tissues of animals is well documented. However, no previous study has examined the ability of TCDD to induce oxidative stress and tissue damage in brain in vivo. In this study the ability of TCDD to induce oxidative stress in brain tissues of mice was studied after subchronic exposures. Groups of female B6C3F1 mice were treated orally with TCDD (0, 0.45, 1.5, 15, and 150 ng/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…A series of more detailed studies on the induction of oxidative stress in brain tissues have been conducted by Hassoun et al [20,84,98,[123][124][125][126]. Oral administration of up to 150 ng TCDD/kg/day to female mice for 13 weeks resulted in dose-dependent increases in whole brain superoxide anion, lipid peroxidation, and DNA single-strand breaks [123].…”
Section: Oxidative Stress and Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A series of more detailed studies on the induction of oxidative stress in brain tissues have been conducted by Hassoun et al [20,84,98,[123][124][125][126]. Oral administration of up to 150 ng TCDD/kg/day to female mice for 13 weeks resulted in dose-dependent increases in whole brain superoxide anion, lipid peroxidation, and DNA single-strand breaks [123].…”
Section: Oxidative Stress and Neurotoxicitymentioning
confidence: 99%
“…Oral administration of up to 150 ng TCDD/kg/day to female mice for 13 weeks resulted in dose-dependent increases in whole brain superoxide anion, lipid peroxidation, and DNA single-strand breaks [123]. The subchronic exposure of female rats to low doses of TCDD and two of its congeners, PeCDF and PCB126, produced dose-dependent increases in brain superoxide anion, lipid peroxidation, and DNA single-strand breaks [98].…”
Section: Oxidative Stress and Neurotoxicitymentioning
confidence: 99%
“…1) Recent studies have demonstrated that oxidative stress is an important constituent in the mechanism of TCDD toxicity. 2,3) The increased production of reactive oxygen species, lipid peroxidation, and DNA and membrane damage are always associated with TCDD exposure. 4) Several studies have suggested that TCDD causes the activation of the aryl hydrocarbon receptor (AhR), which is a ligand-activated transcription factor in most cell and tissue types.…”
mentioning
confidence: 99%
“…[2][3][4] Chitooligosaccharides are known to be biologically active compounds. 5) Chitohexaose and its N-peracetylated derivative were shown to inhibit the growth of murine cancer cells.…”
mentioning
confidence: 99%